Postural control and the influence of the extent of thigh support on dynamic sitting balance among individuals with thoracic spinal cord injury. (March 2020) - Ilha, Jocemar; Abou, Libak; Romanini, Francielle; Dall Pai, Ana Carolina; Mochizuki, Luis
Abstract: Background: Unsupported sitting balance with reduced thigh support is necessary during several daily living activities among individuals with spinal cord injury. This study proposed to compare dynamic unsupported sitting postural control under reduced thigh support conditions in individuals with motor-complete thoracic spinal cord injury and able-bodied individuals. Methods: Thirteen individuals with spinal cord injury and thirteen able-bodied individuals were asked to put on a t-shirt and reach forward while sitting on a force platform using maximum, medium or minimum thigh support extent. Postural control was measured by the center of pressure parameters. Findings: Individuals with spinal cord injury presented larger postural sway parameters and mean velocity of the center of pressure displacement in anterior-posterior direction during the t-shirt wearing task. On the other hand, these parameters were lower in the medial-lateral direction. These results are more expressive when the task was performed in reduced thigh support conditions [F(1, 76) = 5.05–18.70; p < 0.05]. Lower postural sway parameters and mean velocity of the center of pressure displacement in anterior-posterior, and postural sway in medial-lateral direction in the three thigh support conditions were observed when individuals with spinal cord injury performed the forward reaching task [F(1, 76) = 9.81–185.46; p < 0.01]. Interpretation: The results confirm that individuals with motor-complete thoracic spinal cord injury have poor postural stability and show a trunk postural sway constraint to maintain the suboptimal unsupported sitting balance. Reduced thigh support extent can challenge the dynamic sitting balance in individuals with thoracic spinal cord injury and should be indicated to train new and diversified postural control strategies. Highlights: The postural control during dynamic unsupported sitting balance was analyzed. Individuals with thoracic spinal cord injury were compared to able-bodied. The influence of thigh support extent on unsupported sitting balance was analyzed. Individuals with spinal cord injury show a sitting trunk postural sway constraint. Thigh support extent affects dynamic unsupported sitting postural control strategy.